Ascertaining the Curriculum Relevance of the Graduate School through Tracer Study in a Philippine Private Higher Education Institution - David Cababaro Bueno (Philippine Association of Institutions for Research, Inc., 2017)
Graduate education is part of the most effective means of developing capacities related to doing research that will improve educational theory and practice in the many different aspects of the educational process. Thus, the study traced the employability and productivity of the graduates of a Private Higher Education Institution (PHEI)-graduate school from 2010 - 2015 in the Philippines to further improve its curricular offerings. The descriptive-survey design was used. The majority of the graduates of the Doctor of Education (Ed.D.), Master of Arts (MA), Master of Business Administration (MBA) and Master of Project Management (MPM) programs are employed in a regular or permanent status. They are now occupying supervisory and managerial positions and highly satisfied with their basic salary. The graduate curricula are responding to the needs of various industries. Administration and governance, curriculum and instruction, research, professional and cognate courses, student services, library, internet laboratory, interdisciplinary learning, and teaching/ learning environment are the school-related factors relevant to the current employment of the graduates. Communication, human relations, entrepreneurial, information technology, problem-solving, critical thinking, and research skills are considered relevant skills learned. Love of God, honesty, punctuality, obedience to superior, perseverance, creativity, professional integrity, unity, fairness, love for others, nationalism and being eco-friendly are the values evidently manifested in their workplaces. Thus, the graduate school is continuously nurturing and embracing the quality of education.